Implementasi Konsep Amr Ma‘rûf Nahy Munkar Qâdî ‘Abd al-Jabbâr al-Hamadânî Dalam Kitab Sharh al-Usûl al-Khamsah - Akhmad Jazuli Afandi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2014)
Islamic command on amar ma‘rûf nahy munkar has been basically intended for all Muslims regardless of their theological affiliation. Mu‘tazila, however, has a typical understanding of it. Qâdî ‘Abd al-Jabbâr, as one of Mu‘tazili-tes clerics and theologians, who wrote Sharh al-Usûl al-Khamsah discusses the concept of amar ma‘rûf nahy munkar together with its contextual meaning and how to implement it on the real live. This problem is investigated and analyzed by using descriptive methodology, and hermeneutic analysis. From the data collected and analysis conducted it is concluded that amr ma‘rûf nahy munkar in ‘Abd al-Jabbâr thought is considered wâjib al-kifâyah in a sense that it should be in accordance with the capacity and competence of its doers, with the method of treatment ranging from soft to firm action, even with fight whenever necessary to do so. And in order to be able to apply its concept, the Islamic Caller, the Government, the Ulama and Intellectuals and even the Common People must be qualified and fulfill some criteria and standard.